Type and duration of subsyndromal symptoms in youth with bipolar I disorder prior to their first manic episode. (5th March 2014) - Correll, Christoph U; Hauser, Marta; Penzner, Julie B; Auther, Andrea M; Kafantaris, Vivian; Saito, Ema; Olvet, Doreen; Carrión, Ricardo E; Birmaher, Boris; Chang, Kiki D; DelBello, Melissa P; Singh, Manpreet K; et al.
<x xml:space="preserve">Abstract</x> Objectives The aim of the present study was to systematically evaluate the prodrome to mania in youth. Methods New‐onset/worsening symptoms/signs of ≥ moderate severity preceding first mania were systematically assessed in 52 youth (16.2 ± 2.8 years) with a research diagnosis of bipolar I disorder (BD‐I). Youth and/or caregivers underwent semi‐structured interviews, using the Bipolar Prodrome Symptom Scale–Retrospective. Results The mania prodrome was reported to start gradually in most youth (88.5%), with either slow (59.6%) or rapid (28.8%) deterioration, while a rapid‐onset‐and‐deterioration prodrome was rare (11.5%). The manic prodrome, conservatively defined as requiring ≥ 3 symptoms, lasted 10.3 ± 14.4 months [95% confidence interval (CI): 6.3–14.4], being present for ≥ 4 months in 65.4% of subjects. Among prodromal symptoms reported in ≥ 50% of youth, three were subthreshold manic in nature (irritability: 61.5%, racing thoughts: 59.6%, increased energy/activity: 50.0%), two were nonspecific (decreased school/work functioning: 65.4%, mood swings/lability: 57.7%), and one each was depressive (depressed mood: 53.8%) or subthreshold manic/depressive (inattention: 51.9%). A decreasing number of youth had ≥ 1 (84.6%), ≥ 2 (48.1%), or ≥ 3 (26.9%) 'specific' subthreshold mania symptoms (i.e., elation, grandiosity, decreased need for sleep, racing thoughts, or hypersexuality), lasting 9.5 ± 14.9 months (95% CI: 5.0–14.0), 3.5 ± 3.5 months (95% CI: 2.0–4.9), and 3.0 ± 3.2 months (95% CI: 1.0–5.0) for ≥ 1, ≥ 2, or ≥ 3 specific symptoms, respectively. Conclusions In youth with BD‐I, a relatively long, predominantly slow‐onset mania prodrome appears to be common, including subthreshold manic and depressive psychopathology symptoms. This suggests that early clinical identification and intervention may be feasible in bipolar disorder. Identifying biological markers associated with clinical symptoms of impending mania may help to increase chances for early detection and prevention before full mania.